Negative drain-induced barrier lowering and negative differential resistance effects in negative-capacitance transistors. (February 2021) - Yu, Tianyu; Lü, Weifeng; Zhao, Zhifeng; Si, Peng; Zhang, Kai
Abstract: In this study, the negative drain-induced barrier lowering (DIBL) and negative differential resistance (NDR) effects are investigated in detail in negative-capacitance field-effect transistors (NCFETs) with a fully depleted silicon-on-insulator structure. We show that the negative DIBL and NDR effects are caused by a decrease in the internal gate voltage, which is closely related to the matching between the ferroelectric capacitance and the total gate capacitance of the underlying FET. Further, we define the remnant-polarization-to-coercive-field ratio ( R PE ), which can be directly used as a parameter to quantify the DIBL effect and describe the sign of the NDR effect. DIBL tends to be consistent with the same R PE, despite exhibiting different current intensities in the strong inversion region. With regard to different R PE, the DIBL effect decreases but the NDR effect increases as R PE decreases. Our work may provide further insight for NCFET designers to adjust capacitance matching to optimize the DIBL and NDR effects.